Pengembangan Video Tutorial Menjahit Kebaya Kartini Pada Siswa Kelas Xi Di SMKN 2 Jombang - Lilik Vadia Maulida Hanifah; Inty Nahari (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study develops a tutorial video as a learning medium for the skill concentration subject in class XI at SMKN 2 Jombang. The study aims to describe: 1) the feasibility of the Kartini kebaya sewing tutorial video developed, based on expert assessments (material experts, media experts, and language experts); and 2) the responses of class XI students at SMKN 2 Jombang to the Kartini kebaya sewing tutorial video developed as a practical learning medium. The type of research used in this study is the R&D (Research and Development) method, using the 4D research model (define, design, development, disseminate). The research subjects were 32 students of class XI DPB 4 at SMKN 2 Jombang. The data collection techniques used in this study were media feasibility testing and student response questionnaires. The data analysis techniques used were feasibility level analysis of the tutorial video and analysis of the student response questionnaire. The results of the study show that: 1) the validity level of the Kartini kebaya sewing tutorial video, as assessed by material experts, media experts, and language experts, obtained a score percentage of 4.45, categorized as very good; and 2) the results of student responses to the Kartini kebaya sewing tutorial video obtained a score percentage of 99% with "Yes" answers, categorized as very good.